New Formulation and Evaluation of Camptothecin Encapsulated and/or Dispersed Suppository - Fatmi, Sofiane; Taouzinet, Lamia; Lahiani-Skiba, Malika; Skiba, Mohamed; Iguer-Ouada, Mokrane (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Camptothecin is known for its potent anticancer activity. However, its optimal activity is reduced due to its low solubility and stability in biological media. Objective: The aim of the present study is to design and characterize a Camptothecin (CPT) suppository formulation. Methods: Rectal suppositories of camptothecin alone, encapsulated with Cyclodextrin (CD) and in the ternary system (CPT encapsulated with cyclodextrin and dispersed in Polyethylene Glycol (PEG) 6000) were prepared using various hydrophobic and hydrophilic polymeric bases as semi-synthetic glyceride (Suppocire® AM Pellets) and Polyethylene Glycols (PEGs) mixtures. Formulations were evaluated by various parameters like weight variation, drug content, hardness and liquefaction time. In vitro release study was performed in USP type I apparatus using phosphate buffer pH 7.2 as dissolution media. Results: Suppositories were within the permissible range of all physical parameters. In vitro drug released from water soluble base (PEG) was greater than that from oil soluble base with ninety percent (90%) of drug dissolution. It was also established that drug release from various formulations was by diffusion mechanism, according to the Higuchi’s equation. Conclusion: This new formulation offers a new approach to colorectal cancer treatment by offering an alternative and simple drug administration route.
Keywords: colorectal cancer